Pemakaian Sel HeLa dalam Uji Sitotoksisitas Fraksi Kloroform dan Etanol Ekstrak Daun Annona squamosa - IRA DJAJANEGARA; PRIO WAHYUDI (JURNAL ILMU KEFARMASIAN INDONESIA, 2009)
Custard apple (Annona squamosa) is a favorite fruit in Indonesia. The leave of this plant is used and known for long time as an astringent, antiinflammatory, birth control, and antitumor agents. Previous experiments on toxicity using brine shrimp lethality test (BSLT) method indicated that the chloroform fraction of custard apple leaves was toxic to the shrimp larvae with LC50 value at 1.77µg/ml. This experiment was carried out to investigate further the possible role of custard apple leaves as an anticancer agent using HeLa cell line. Experiment was initiated by extracting the leaves using 70% ethanol by means of maceration. The macerate was then fractionated further using chloroform as solvent. The ethanol fraction and chloroform fraction were used in cytotoxicity assay using (cervix cancer) HeLa cell line. Cytotoxicity assay Was done using direct counting method. The amount of living cells were observed and counted, death percentage Was then determined and probit analysis Was applied to determine the LC50 value. LC50 value for ethanol fraction from the leaves of custard apple (Annona squamosa) Was 7.695 µg/ml While for chloroform fraction was 4.547 µg/ml based on cytotoxicity analysis using HeLa cells. This experiment concluded that theleaves of custard apple (Annona squamosa) has cytotoxicity toward HeLa cell lines which confirmed the previous toxicity experiment using brine shrimp lethality test (BSLT) method. Overall, this experiment indicated that the leaves of custard apple (Annona squamosa) have anticancer activity.